Deterministic enhancement of coherent photon generation from a nitrogen-vacancy center in ultrapure diamond - Riedel, Daniel; Sollner, Immo; Shields, Brendan J.; Starosielec, Sebastian; Appel, Patrick; Neu, Elke; Maletinsky, Patrick; Warburton, Richard J. (Physical Review X, 2017)
The nitrogen-vacancy (NV) center in diamond has an optically addressable, highly coherent spin. However, a NV center even in high-quality single-crystalline material is a very poor source of single photons: Extraction out of the high-index diamond is inefficient, the emission of coherent photons represents just a few percent of the total emission, and the decay time is large. In principle, all three problems can be addressed with a resonant microcavity. In practice, it has proved difficult to implement this concept: Photonic engineering hinges on nanofabrication, yet it is notoriously difficult to process diamond without degrading the NV centers. Here, we present a microcavity scheme that uses minimally processed diamond, thereby preserving the high quality of the starting material and a tunable microcavity platform. We demonstrate a clear change in the lifetime for multiple individual NV centers on tuning both the cavity frequency and antinode position, a Purcell effect. The overall Purcell factor FP ¼ 2.0 translates to a Purcell factor for the zero phonon line (ZPL) of FZPLP ∼ 30 and an increase in the ZPL emission probability from about 3% to 46%. By making a step change in the NV’s optical properties in a deterministic way, these results pave the way for much enhanced spin-photon and spin-spin entanglement rates.
CRIS-Team Scopus Importer:2023-03-27